Impact of Daily Exercise Compared to Exercise on Alternating Days on Post-Exercise Blood Pressure Reduction in Men with Elevated Blood Pressure - Zachary Zeigler; Malachi Votaw; Connor Dreos; Lydia Durnil; Jamie Terran; Danielle Akin; Trevor Nordin (Sapientia Publishing Group, 2018)
Objectives Acute exercise can result in post-exercise hypotension (PEH) lasting up to 24-h. Whether exercise performed on consecutive days would lead to an accumulating PEH effect has yet to be determined. The purpose of this study was to compare daily exercise (DE) to exercise performed on alternating days (AE) and control (CON) on PEH. Methods Sedentary men 18-30 yr with elevated blood pressure (BP) participated in this three-arm randomized cross-over trial. The primary comparison was PEH between three groups (CON, AE, DE) over time (day 1,2,3). Both exercise groups were prescribed the same exercise intensity (70-75%HRmax), and total duration of exercise (90min) on a cycle ergometer. DE performed exercise on three consecutive days (three bouts 30min). AE performed exercise on two alternating days (2 bouts 45min). Following exercise subjects remained in the laboratory for 1-h while BP was taken every 5-min. Results Nine overweight (BMI=29.2±4.5kg/m2), young (22.7±2.4years), moderately fit (VO2peak=35.6±7.3 ml.kg.min), male subjects with elevated BP (126.2±10.4 and 73.3±6.4 mmHg) completed the study. There was a significant systolic BP condition by day effect such that on day three systolic BP (CON 119.0±9.3, AE 118.9±15.0, DE 115.0±11.9 mmHg), and diastolic BP (CON 71.9±6.6, AE 68.4±10.3, DE 67.6±6.2 mmHg) were lowest during the post-exercise DE condition (P<0.001). Additionally, DE saw a significant reduction of resting systolic BP between day 1 and day 4 (122.8±10.2 mmHg vs 113.1±12.0 mmHg; P=0.022, respectively) and a borderline significant reduction between day 1 and day 3 (122.8±10.2 mmHg vs 114.8±10.0 mmHg; P=0.051, respectively). DE saw a borderline significant resting diastolic BP reduction between day 1 and day 3 (73.2±7.2 mmHg vs 68.6±6.5 mmHg; P=0.058, respectively) and a significant reduction between day 1 and day 4 (73.2±7.2 mmHg vs 66.4±4.3 mmHg; P=0.022, respectively). Conclusions In conclusion, the post-exercise BP lowering effect of the prior exercise session appeared to accumulate during DE such that day 3 was the lowest of all conditions and days.